Pengembangan Modul Ajar Berdiferensiasi Berbasis ADDIE pada Mata Pelajaran Bahasa Indonesia di SMK Negeri 2 Bojonegoro - Yunita, Vika; Sujinah, Sujinah; Yarno, Yarno (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study also aims to describe the validity, effectiveness of the development of differentiated teaching modules to increase students' creativity in making observation reports. This research uses the R&D (Research and Development) method with ADDIE's development steps consisting of several stages: Analysis, Design, Development, Implementation and Evaluation. The assessment instrument used by the researcher is in the form of a validation and practicality sheet, then the assessment instrument is validated by three validators, namely content validators, language validators and graphics validators, then the practicality sheet is determined by practitioners. The results of the validity of the Teaching Module carried out by the validator team obtained an average validity score of 9% categorized as very valid. Furthermore, the results of the effectiveness test showed the completeness of students' effective student learning outcomes with an average score of 92%. In addition, the average score of the practicality test results by educators of 93.45% is categorized as very practical. The results of the development of differentiated teaching modules are very valid, effective, and practical in increasing students' creativity in making reports on observation results in Indonesian Language subjects.